Meta-analyses of cognitive and motor function in youth aged 16 years and younger who subsequently develop schizophrenia - Dickson, Hannah; Hodgins, Sheilagh (Psychological medicine, 2012)
Background. Previous reviews have reported cognitive and motor deﬁcits in childhood and adolescence among individuals who later develop schizophrenia. However, these reviews focused exclusively on studies of individuals with aﬀected relatives or on population/birth cohorts, incorporated studies with estimated measures of pre-morbid intelligence, or included investigations that examined symptomatic at-risk participants or participants 18 years or older. Thus, it remains unclear whether cognitive and motor deﬁcits constitute robust antecedents of schizophrenia. Meta-analyses were conducted on published studies that examined cognitive or motor function in youth aged 16 years or younger who later developed schizophrenia or a schizophrenia spectrum disorder (SSD) and those who did not. Method. Twenty-three studies fulﬁlled the following inclusion criteria : (1) written in English ; (2) prospective investigations of birth or genetic high-risk cohorts, or follow-back investigations of population samples ; (3) objective measures of cognitive or motor performance at age 16 or younger ; (4) results provided for individuals who did and who did not develop schizophrenia/SSD later in life ; and (5) suﬃcient data to calculate eﬀect sizes. Four domains of function were examined : IQ ; Motor Function ; General Academic Achievement ; and Mathematics Achievement. Results. Meta-analyses showed that, by age 16, individuals who subsequently developed schizophrenia/SSD displayed signiﬁcant deﬁcits in IQ (d=0.51) and motor function (d=0.56), but not in general academic achievement (d=0.25) or mathematics achievement (d=0.21). Subsidiary analysis indicated that the IQ deﬁcit was present by age 13. Conclusions. These results demonstrate that deﬁcits in IQ and motor performance precede the prodrome and the onset of illness.
Published online: 06 September 2011
Gesehen am 17.12.2018